2022
DOI: 10.1108/ajim-12-2021-0383
|View full text |Cite
|
Sign up to set email alerts
|

What influences user participation in an online health community? The stimulus-organism-response model perspective

Abstract: PurposeThe purpose of this paper is to understand the effect of platform characteristics (i.e. media richness and interactivity) on individual perception (i.e. outcome expectations) and consequent behavioral response (i.e. user participation in online health communities (OHCs)) based on the stimulus-organism-response (S-O-R) model.Design/methodology/approachThis study developed a research model to test the proposed hypotheses, and the proposed model was tested using partial least squares structural equation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Although this model was developed in environmental psychology, many researchers have used this framework to examine individuals’ behavioral responses in different research areas such as store environment, online learning, online social networks, and online video watching ( Vieira, 2013 ; Zhai et al, 2020 ; Masrom et al, 2021 ; Wang and Yue, 2022 ). In the fields of online health and fitness, recent studies also utilizing the S-O-R theory have demonstrated the effect of platform characteristics as environmental stimuli on individuals’ internal reactions and consequent behavioral responses related to fitness applications and community ( Elsotouhy et al, 2022 ; Teng and Bao, 2022 ; Zhou et al, 2022 ). However, researchers have paid little attention to applying this framework in short fitness videos.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Although this model was developed in environmental psychology, many researchers have used this framework to examine individuals’ behavioral responses in different research areas such as store environment, online learning, online social networks, and online video watching ( Vieira, 2013 ; Zhai et al, 2020 ; Masrom et al, 2021 ; Wang and Yue, 2022 ). In the fields of online health and fitness, recent studies also utilizing the S-O-R theory have demonstrated the effect of platform characteristics as environmental stimuli on individuals’ internal reactions and consequent behavioral responses related to fitness applications and community ( Elsotouhy et al, 2022 ; Teng and Bao, 2022 ; Zhou et al, 2022 ). However, researchers have paid little attention to applying this framework in short fitness videos.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Thus, the SOR model has been examined to explain user online behavior (e.g. Zhou et al, 2022), purchase intention (e.g. Zhu et al, 2020) and social commerce intention (e.g.…”
Section: Literature Review and Hypotheses Development 21 Sor Modelmentioning
confidence: 99%